2016
DOI: 10.1055/s-0035-1558289
|View full text |Cite
|
Sign up to set email alerts
|

Thymoquinone from Nigella sativa Seeds Promotes the Antitumor Activity of Noncytotoxic Doses of Topotecan in Human Colorectal Cancer Cells in Vitro

Abstract: Topotecan, a topoisomerase I inhibitor, is an anticancer drug widely used in the therapy of lung, ovarian, colorectal, and breast adenocarcinoma. Due to the primary dose-limiting toxicity of topotecan, which is myelosuppressive, it is necessary to identify other chemotherapeutic agents that can work synergistically with topotecan to increase its efficacy and limit its toxicity. Many studies have shown synergism upon the combination of topotecan with other chemotherapeutic agents such as gemcitabine. Other stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(39 citation statements)
references
References 34 publications
2
37
0
Order By: Relevance
“…In addition to the induction of synergistic cytotoxic effects through interference in tumor growth and survival signaling, combination treatment with TQ also exhibited chemo-protective effects and limited organ toxicity (Brown et al, 2014). Numerous other studies have investigated the potential chemo-potentiating effects of TQ with diverse classes of chemotherapeutic drugs (summarized in Table 1) including anti-estrogen (e.g., tamoxifen), topoisomerase-I inhibitor (e.g., topotecan), and microtubule disrupting agents (Rajput et al, 2013; Khalife et al, 2014, 2016; Dirican et al, 2015; Ganji-Harsini et al, 2016; Sakalar et al, 2016). Rajput et al recently reported that TQ can cause reversal of tamoxifen resistance in triple negative breast cancer cells by interfering in Akt-mediated induction of apoptosis inhibitory protein such as X-linked inhibitor of apoptosis protein (XIAP; Rajput et al, 2013).…”
Section: Chemo-potentiating Role Of Tqmentioning
confidence: 99%
“…In addition to the induction of synergistic cytotoxic effects through interference in tumor growth and survival signaling, combination treatment with TQ also exhibited chemo-protective effects and limited organ toxicity (Brown et al, 2014). Numerous other studies have investigated the potential chemo-potentiating effects of TQ with diverse classes of chemotherapeutic drugs (summarized in Table 1) including anti-estrogen (e.g., tamoxifen), topoisomerase-I inhibitor (e.g., topotecan), and microtubule disrupting agents (Rajput et al, 2013; Khalife et al, 2014, 2016; Dirican et al, 2015; Ganji-Harsini et al, 2016; Sakalar et al, 2016). Rajput et al recently reported that TQ can cause reversal of tamoxifen resistance in triple negative breast cancer cells by interfering in Akt-mediated induction of apoptosis inhibitory protein such as X-linked inhibitor of apoptosis protein (XIAP; Rajput et al, 2013).…”
Section: Chemo-potentiating Role Of Tqmentioning
confidence: 99%
“…It was also cytotoxic toward A549 lung carcinoma and DLD-1 colon adenocarcinoma cells (IC 50 = 13 and 5.9 μM, respectively; Bourgou et al, 2010). Khalife et al (2016) described that the cytotoxic effect was dose- and time-dependent (IC 50 = 59.2 and 68.4 μM, for 24 and 48 h, respectively) for HT-29 colorectal carcinoma cells. Woo et al (2011) described the cytotoxic effect of thymoquinone against different breast cancer lines with MDA-MB-231 cells as the most susceptible ones (IC 50 = 11 μM after 48 h).…”
Section: Scientific Evidence and Mechanisms Of Actionmentioning
confidence: 99%
“…Thus, only studies with its major compound (thymoquinone) will be referred. Thymoquinone was able to cause cell cycle arrest at S phase (Khalife et al, 2016). By contrast, Woo et al (2011) described that this compound caused accumulation of cells in the sub-G1 phase without effect on p53 activation.…”
Section: Scientific Evidence and Mechanisms Of Actionmentioning
confidence: 99%
“…The cytotoxic activities of our most active compounds 4d and 4j were compared with those of the commercially available Topotecan, 16) Irinotecan, 17) Etoposide, 18) Tamoxifen, 19) and Cisplatin. 20) As shown in Table 3, compound 4d (3-OH) was ten times more active than cisplatin in the prostate PC-3 cell line, almost two thousand times more active than irinotecan in the colon HCT-15 cell line.…”
Section: Resultsmentioning
confidence: 99%